Supply Chain Risk Management Design for U-Hansa Product in Relation to Covid-19 Pandemics - Friesca Erwan; Prima Denny Sentia; Zaty Fadhilla; Didi Asmadi; Raihan Dara Lufika; Rizki Agam Syahputra (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
The recent Covid-19 pandemics situation has brought a lot of discussion on how to manage a supply chain in uncertainty since the dynamic of pandemics risk has altered the way a supply chain is organized. This research aims to identify, asses and manage the possible risks on supply chain that may occur in relation to production process of U-Hansa (USK Hand Sanitizer) following a high demand of hand sanitizer during the pandemics. This research performed risk breakdown structure to identify risks, evaluated the risks using risk matrix 5x5 (MIL-STD-882B) and create risk mapping using the big picture approach. This research revealed that there are 15 risks involved in U-Hansa production process that can potentially disrupt the whole supply chain process of U-Hansa. Factors such as raw material shortage during the Covid-19 lockdown, insufficient production capacity and the limitation of machinery and equipment to support the production contributes to the noticeable risk potential in the overall U-Hansa supply chain network. The overall findings of this research are expected to help the decision-making process that can be utilized in the post-Covid-19 pandemics setting.